FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN GIZI LEBIH PADA PEGAWAI DI SMPN 4 PASARKEMIS TAHUN 2023 - Tasya Annisa Zahrani (2023)
Overnutrition is often associated with overweight and obesity caused by the accumulation of excess fat that can interfere with one's health. The majority of employees over 18 years old are obese which can interfere with productivity at work. This study aims to determine the relationship between knowledge of balanced nutrition, physical activity, breakfast habits and frequency of consumption of risky foods (sweet and fatty) with the incidence of overnutrition in employees at SMPN 4 Pasarkemis. This study used a cross-sectional design with a sampling technique, namely Quota Sampling. The sample used in this study was 54 employees. Data collection was done using a questionnaire. The data obtained were tested using the Fisher Exact Test. The results of the analysis showed that there was a relationship between breakfast habits (p=0,039) and physical activity (p=0,044) with the incidence of overweight and there was no relationship between knowledge of balanced nutrition (p=0,5) and frequency of consumption of risky foods (sweet and fatty) (p=0,244) with the incidence of overweight.